Association between reduced lung function, hydration and nutritional status in patients on hemodialysis: An observational study using bioelectrical impedance vector analysis (BIVA) - Sheila Borges; Angela Teodósio da Silva; Taís Ferreira Martins; Letícia de Araújo Morais; Felipe Vilaça Cavallari Machado; Gerson Cipriano Júnior; Graziella França Bernardelli Cipriano (Clinical Nutrition Open Science)
Summary: Background & aims: This study aimed to determine the lung function and to investigate the association between pulmonary parameters, hydration, and nutritional status – assessed by bioelectrical impedance vector analysis (BIVA) – in patients on HD. Methods: A cross-sectional study, including patients with CKD on HD, age >18 years. Laboratory data, lung function and body composition by bioimpedance were evaluated. Results: The sample consisted of 42 participants, 23 (55%) male and age 54±14 years. Reduced lung function was prevalent in 30 (71%) participants, and compared to those with preserved lung function, they had higher dialysis vintage, lower body weight, body mass index, adipose tissue mass and fat tissue. Regarding hydration status and bioimpedance parameters, participants with reduced lung function had significant difference in the variable overhydration (OH) (P = 0.034). OH, phase angle (PhA) and reactance (Xc) correlated with forced vital capacity (FVC) and forced expiratory volume in 1st second (FEV1). Regarding BIVA, the mean vector of patients with reduced lung function indicated hyperhydration and malnutrition and the mean vector of preserved lung function indicated normohydration and adequate nutritional status. The multivariate logistic regression analysis to determine predictors of reduced lung function showed that OH was significantly associated with this condition. Conclusions: Participants with reduced lung function had lower weight, body mass index, fat tissue and hyperhydration, consequently, bioimpedance parameters (OH, PhA and Xc) were correlated with respiratory variables. Fluid status was a predictor of reduced lung function in patients on HD.